Thyrotropin Regulates IL-6 Expression in CD34(+) Fibrocytes: Clear Delineation of Its cAMP-Independent Actions - Raychaudhuri, Nupur (Public Library of Science, 2013)
IL-6 plays diverse roles in normal and disease-associated immunity such as that associated with Graves’ disease (GD). In that syndrome, the orbit undergoes remodeling during a process known as thyroid-associated ophthalmopathy (TAO). Recently, CD34(+) fibrocytes were found to infiltrate the orbit in TAO where they transition into CD34(+) orbital fibroblasts. Surprisingly, fibrocytes display high levels of functional thyrotropin receptor (TSHR), the central antigen in GD. We report here that TSH and the pathogenic anti-TSHR antibodies that drive hyperthyroidism in GD induce IL-6 expression in fibrocytes and orbital fibroblasts. Unlike TSHR signaling in thyroid epithelium, that occurring in fibrocytes is completely independent of adenylate cyclase activation and cAMP generation. Instead TSH activates PDK1 and both AKT/PKB and PKC pathways. Expression and use of PKCβII switches to that of PKCµ as fibrocytes transition to TAO orbital fibroblasts. This shift is imposed by CD34(−) orbital fibroblasts but reverts when CD34(+) fibroblasts are isolated. The up-regulation of IL-6 by TSH results from coordinately enhanced IL-6 gene promoter activity and increased IL-6 mRNA stability. TSH-dependent IL-6 expression requires activity at both CREB (−213 to −208 nt) and NF-κB (–78 to −62 nt) binding sites. These results provide novel insights into the molecular action of TSH and signaling downstream for TSHR in non-thyroid cells. Fibrocytes neither express adenylate cyclase nor generate cAMP and thus these findings are free from any influence of cAMP-related signaling. They identify potential therapeutic targets for TAO.